Sphingosine-1-phosphate: A bioactive lipid that confers high-density lipoprotein with vasculoprotection mediated by nitric oxide and prostacyclin - Rodríguez, Cristina; González-Díez, María; Badimon, Lina; Martínez-González, José (Thrombosis and Haemostasis, 2009)
Sphingosine-1-phosphate (S1P) is a bioactive lipid generated in the intracellular membranes from the metabolism of sphingomyelin. Once secreted/exported by cells of haematopoietic origin and vascular cells S1P interacts with plasma proteins and accumulates in high-density lipoprotein (HDL). Growing evidence indicates that HDL-associated S1P is responsible for the beneficial effects of these lipoproteins on vasorelaxation, cell survival, cell adhesiveness, angiogenesis and synthesis of two powerful endogenous anti-atherogenic and anti-thrombotic molecules such as nitric oxide (NO) and prostacyclin (PGI2). It is likely that vascular effects of HDL-S1P are regulated by the local expression of S1P receptors. Five G protein-coupled receptors (S1P1 to S1P5), with differential expression patterns and dissimilar coupling mechanism to G protein subunits, have been identified in the vasculature. This review is focused on the central role of S1P as a bioactive component that confers vasculoprotective properties to HDL by eliciting a wide range of biological responses on endothelial and smooth muscle cells largely dependent on the up-regulation of NO and prostacyclin.
Keywords: High-density lipoproteins; sphingosine-1-phosphate; prostacyclin; nitric oxide; vascular function